Measuring Success: Western ABC's, Paul's XYZ's & Ubuntu as Markers for Church Growth in Africa - Davis, C. Bryan (Transformation, 2024)
Traditional measures of church growth, such as attendance and giving, come from aspects of growth that can readily be counted. These countable measures resonate with cultural assumptions about success, in which more is better. In contrast, the Apostle Paul offers a measure of church growth built around conforming to the kenotic example of Christ, in which Christ emptied Himself of divine power and took on the form of a slave to serve humanity (Phil. 2:6–8). In Paul's paradigm, the necessary indicator of church growth is how well believers follow Christ's example of servanthood by living in Christian community. The present paper uses the communitarian values associated with ubuntu to provide a framework for understanding Paul's kenotic paradigm of church growth in the African context.